Pneumonia associada à ventilação mecânica: Impacto da resistência bacteriana, dos erros de prescrição e descalonamento de antimicrobianos na mortalidade - Oliveira, Ana Carolina Souza (2015)
Ventilator-associated pneumonia (VAP) is the most prevalent nosocomial infection in intensive care unit (ICU), associated with high mortality rate (14-70%). The objective of this study is evaluate the factors that influence the death of patients with VAP, especially bacterial resistance, prescription errors and de-escalation of antibiotics. Was developed a retrospective study in adult ICU of the Federal University of Uberlândia, which included 120 patients with VAP. We used the chi-square test for qualitative variables, the Student t test for quantitative variables and multiple logistic regression to determine the predictors of mortality.Was identified high mortality of VAP (35%), with a high rate of antimicrobial resistance. The de-escalation of antibiotics and the presence of resistant bacteria had no effect on mortality. The more frequent error prescription of antibiotics was the delay in the start of antibiotic (64.4%). Among the antibiotic prescription errors, patients using incorrect attack dose died 4 times more (P = 0.031) and who did not correction by renal function died 3 times more (P = 0.000). The multiple logistic regression analysis found that the incorrect adjustment for renal function was the only factor that interfered in mortality (1,803-42,531, R² de 0,469). In conclusion, antibiotic prescription errors influenced mortality of patients with VAP, stressing that adequate treatment of VAP is still a challenge that deserves to be continually reassessed, so that the expected clínical response to therapy be guaranteed.